Promotional marketing - Mullin, Roddy (Routledge, 2018)
In today's connected world, promotion is fundamental to everything we do to drive business. This is a new edition of an established book, updated with the latest research on the shopper/buyer and how to reach their 'tipping point' when the decision to buy is made, now covering mobile, online and bricks-and-mortar sales and marketing. This book clarifies why a focus on the customer is key, and how to communicate with them from even before they discover a want or need, to the point of purchase and after. The author of this important book explains how and when to use suppliers (agencies, printers, insurers, et cetera) for promotions of all types, including advertising (outdoor, on websites and in print), experiential marketing (road and trade shows, exhibitions, merchandising) and sales promotions (in-store/web and mobile promotion offers). Processes describe and explain how to implement promotional marketing to achieve business objectives. Promotional Marketing is a practitioner guide to sales and marketing for agencies, entrepreneurs and small businesses and those seeking a career in retail. It is packed with real-life and award-winning case studies and practical briefs (NatWest, Diageo, Sainsbury's, Shell and Radisson, for example) as a starter for when the client needs a creative answer yesterday! It is also tuned to those studying, providing a chapter on how marketing and sales fit into business.